Climate change impacts on agriculture and livelihoods in Sirdibas, Manaslu conservation area, Gorkha - Rai, Ashish; Rijal, Deepak K (Journal of Agriculture and Environment, 2014)
This research assesses impacts of climate change in agriculture and livelihood at Sirdibas village, Gorkha district. Apart from the review of literature, analysis of climatic and socioeconomic data, field data were collected using some selected participatory tools techniques and household survey. The analysis revealed an increased trend on mean annual temperature at the rate of 0.05°C/year while annual mean rainfall is increasing at the rate of 0.995 mm/year while the winter rainfall was in decreasing trend. Increased dry spell and rise in temperature have reduced cropping period both for summer and winter crops. An increased productivity of maize, wheat and millet over years has shown a decreasing trend in the recent years, due to intense off season rainfall followed by water logging. Shifting of farming communities to other businesses also decreased crop yield. Out-migrations have caused decreased crop yield. Along with climate change impacts change, government policy and shifting peoples' livelihood options have impacted agriculture.